Extracellular Vesicles and Interleukins: Novel Frontiers in Diagnostic and Therapeutic for Cancer - Souza, Aline G.; Colli, Leandro M. (Frontiers in Immunology, 2022)
Tumor cells present many strategies for survival and dissemination in the tumor environment. Extracellular vesicles are a vital pathway used in crosstalk between tumor and non-malignant cells. They carry different types of molecules that, when internalized by target cells, can activate signaling pathways and molecular processes that will promote and disseminate neoplastic cells. Proteins, nucleic acids, and different cytokines, such as interleukins, are the main classes of molecules carried by extracellular vesicles and are being studied to understand the molecular mechanisms present in the tumor microenvironment. In particular, although poorly understood, the association between EVs and interleukins has revealed potential approaches to the diagnosis and therapeutics of several neoplasms.